Perancangan Ornamen "Harini" Melalui Kajian Visual Relief Latitavistara pada Candi Borobudur - Noor Latif CM (Humaniora, 2014)
Indonesia has many ornaments given that various cultures born in this archipelago. Variety of ornaments that characterizes a region refers to such cultural relics from the past. Excavation of the ornaments through the relics of the past with a rich in visual such as Borobudur may lead to the birth of the spirit of love of local product which is based on culture and tradition. Latitavistara relief which is part of the past Buddhist fragment became the main object in extracting visual object to bear a new visual language in the form of ornaments. The design of the ornament with a new visual appearance only used the visual elements of the flora in Latitavistara relief classified according to its clump type. The method used in this visual design referred to the simplification of the form leading to the symbolization inherent to the religious philosophy of Borobudur. Division levels in the pursuit of perfection contained in Borobudur were basis for determining the variations of ornament design generated. The results of this ornament design are expected to be applied into other visual disciplines which is not always be just a mere craft product. The spirit of recycling cultural heritage and traditions of the past to be a creative product with modern innovation becomes inseparable part of this design.